Enhancing Entrepreneurial Mindset and Business Strategies of Student Tenants through Mentoring at EXSIS Ramadhan 2026 - Evi Ramadhani; Basri Effendi; Khoirul Amri; Nurul Kamal; Sayyid Afdhal El Rahimi; Wira Nahma Griantara (Universitas Syiah Kuala, 2026)
Student entrepreneurship programs in higher education often face challenges related to limited practical experience, the ability to respond to market dynamics, and mental readiness to deal with business failure. This condition was also experienced by students and recent graduate tenants participating in EXSIS Ramadhan Universitas Syiah Kuala 2026, who were directly managing their businesses during the Ramadan period. This community service activity aimed to strengthen the entrepreneurial capacity of the tenants through a reflective mentoring program entitled Failed Business vs. Successful Business: From Failure to Business Success. The implementation method included problem identification, mentoring material design, online delivery through Zoom, interactive discussion, and evaluation based on observation and participant feedback. The results showed that the mentoring activity provided practical insights relevant to the tenants’ actual business problems, particularly in terms of promotion strategies, repeat orders, stock management, product quality, pricing, and operational discipline. The activity also strengthened participants’ understanding that business failure is part of the learning process and can be used to improve business strategies in a sustainable manner. Therefore, this mentoring activity contributed to strengthening the mindset, practical knowledge, and adaptive capacity of young entrepreneurs in the higher education environment.